The Cedell method (cerclage wire and staple) leads to less reoperations than the AO method: A retrospective comparative study of 347 lateral ankle fractures. (4th May 2015) - Berggren, Sara S; Tiderius, Carl Johan
Abstract : Background and purpose — Fractures of the lateral malleolus often require open reduction and internal fixation (ORIF). Despite uneventful fracture healing, many patients will suffer from long-term detriments after ORIF, such as local tenderness that requires hardware removal. In Sweden, there are 2 major fixation methods, either the AO method (plate and screws) or the Cedell method (cerclage wire and staple). The purpose of this study was to establish whether there is a difference in extraction frequency between the 2 methods. Patients and methods — We performed a retrospective comparative study of all isolated fractures through the lateral malleolus that were operated at Skåne University Hospital, Sweden, during the period January 2007 to December 2010. 347 patients fulfilled the inclusion criteria (dislocated Weber B isolated fractures of the lateral malleolus) and were categorized according to fixation method. The numbers of reoperations, with preceding indication, were established from the charts. The median follow-up time was 59 (38–86) months after the primary surgery. Results — 22% of the 110 patients treated with the AO method underwent a reoperation, as compared to 8% of the 237 patients treated with the Cedell method (p < 0.001). The median time to extraction was 16 (4–55) months. Interpretation — Less implant removal is needed with the Cedell method than with the conventional AO method. This favors the use of the Cedell method in uncomplicated Weber B lateral ankle fractures, provided that other clinical parameters are comparable.